Konsep Robot Penjaga Toko Di Kombinasikan Dengan Pengendalian Virtual Reality (VR) Jarak Jauh - Kumala Dewi, Nur; Mulyana, Iwan; Syah Putra, Arman; Rasyi Radita, Fatrilia (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
In this study, the authors raised a research on one of the sophistication of artificial intelligence technology, namely robots, the development of robots that are very sophisticated which resemble humans. The research method used is to use a literature review based on books, journals and other literacy that can be used as the basis of research, with a lot of literacy which will add to the knowledge of the researcher and deepen the knowledge of the problems raised in the research. In some countries, robots have been fully utilized and have begun to replace human tasks, for example in Japan, robots have been employed in restaurants and hotels, with robots being employed, human jobs have begun to decrease. This research produces a framework if robots are employed in the retail or shopping sector, with this framework producing suggestions for the development of robotics in Indonesia